ANALYSIS OF THE BALANCE OF MICROFLORA AND PLAQUE IN THE GROWTH AND PROCESS OF MINERALIZATION IN CHRONIC GENERALIZED PERIODONTITIS - Jaxonaliev.B.U (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article provides information on the fact that the structures of the oral cavity of military personnel in extreme climatic conditions cause significant physiological and biochemical changes, the protective mechanisms of dental tissues and oral mucosa weaken, and mineral metabolism is disturbed.